2019
DOI: 10.1080/21663831.2019.1604441
|View full text |Cite
|
Sign up to set email alerts
|

Relating structural heterogeneity to β relaxation processes in metallic glasses

Abstract: The β relaxation is a crucial feature in metallic glasses (MGs). However, its structural origin is not fully elucidated. Using a contact resonance atomic force microscope, we investigated the local structural heterogeneity of MGs and its correlation with β relaxations. It was found that MGs have various degrees of the heterogeneity, resulting in different intensities of β relaxations. Local zones with a prominent heterogeneity lead to a broad energy state distribution and more pronounced β relaxation. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 36 publications
4
17
0
2
Order By: Relevance
“…For glasses rejuvenated by HPT or other methods (i.e., by affine cryogenic deformation, elastostatic loading, cold rolling, shot peening, uniaxial compression, triaxial compression) a fair amount of enthalpy relaxation is observed 4 , 6 , 9 , 34 , 35 in the temperature range characteristic for the β -transition. In the range of the β -transition recent literature reported that some glasses tend to stiffen in DMA 16 , 36 due to annihilation of free volume. It can hence be assumed, that rejuvenation and the β -transition are related.…”
Section: Resultsmentioning
confidence: 99%
“…For glasses rejuvenated by HPT or other methods (i.e., by affine cryogenic deformation, elastostatic loading, cold rolling, shot peening, uniaxial compression, triaxial compression) a fair amount of enthalpy relaxation is observed 4 , 6 , 9 , 34 , 35 in the temperature range characteristic for the β -transition. In the range of the β -transition recent literature reported that some glasses tend to stiffen in DMA 16 , 36 due to annihilation of free volume. It can hence be assumed, that rejuvenation and the β -transition are related.…”
Section: Resultsmentioning
confidence: 99%
“…前期研究通 过实验手段、数值模拟和理论分析已证实微观结构非 均匀性是金属玻璃的内在特征, 这为深入研究金属玻 璃的微观变形机制、微观结构非均匀性与其物理、力 学和化学性能之间的关联提供了有力的依据 [4,14,15] . 属玻璃保留了液体绝大部分的结构信息, 所以弛豫行 为是非晶态材料特别是金属玻璃的内在本质特征之 一 [16,18] . 金属玻璃的弛豫行为受其所处能量状态影响.…”
Section: 引言unclassified
“…一方面, 玻璃转变温度以下的物理时效会增加金属玻 璃微观结构短程有序度甚至长程有序度. 研究表明, 在玻璃转变温度以下物理时效会诱导Zr基和Pd基金属 玻璃局部结构弛豫, 甚至在室温时效作用下La基金属 玻璃也会发生局部结构弛豫 [16,18,20] ; 另一方面, 应变幅 值低于弹性极限的循环加载被视为"力学时效", 金属 玻璃在连续循环加载后向更稳定状态跃迁 [21][22][23] . 基于 前期研究, 力学处理和热学处理对金属玻璃弛豫行 为、力学性能和塑性等的影响引起了研究者广泛的研 究兴趣.…”
Section: 引言unclassified
“…The mentioned impact is one of the widespread pre-treatments such as isothermal annealing [18] and chemical processing [19], which are used at the technology of different materials. The results in this field can broad understanding of the physical processes, related to β-relaxation [20] and hardening because of a strong impact of loading and temperature on continual structure. Moreover, isothermal creep is well investigated both theoretically [21] and experimentally [22] right now, but there are few works on modelling of deformation in metallic glasses at non-stationary conditions (for example, at dynamic mechanical analysis-DMA).…”
Section: Introductionmentioning
confidence: 99%